Biomass properties of short rotation plantations of two Gmelina arborea clones in three spacings - Tenorio, Carolina (2019)
The knowledge of biomass properties from Gmelina arborea clones Roxb in energy crops in short rotation crops systems (SRC) in Costa Rica is limited. The first attempts are based on the use of clones for the production of wood, but planted in SRC. Thus, the present study aimed to evaluate the physical properties (specific gravity, density and moisture content), energy (net calorific value, ash content and volatile materials) and carbon content of two clones of G. arborea used for wood production, but planted in SRC under three spacings (1.0x1.0 m, 0.75x0.75 m and 1.0x0.5 m), between 6 and 24 months of age. Results show that the basic specific gravity was between 0.30 to 0.38, the green density of 0.9 to 1.0 g/cm3, the moisture content between 40 and 70 %, the net caloric value of 18,000 a 20,000 kJ/kg, ash content was less than 4.8 % and the volatile content between 70 and 86%, while the carbon content decreased with age. Differences were observed between the two clones at early ages, but they tend to disappear with increasing age, especially at the age of 24 months, which is when the plantation is intended to be harvested, this being an advantage since we have a uniform biomass if the two clones are used.